Virtual Immediate Coding - V. Kotenko, V; I. Polyakov, A (International Journal of Engineering and Technology, 2018)
A distinctive feature of virtualization of noise-immune encoding is the realized possibility of complex solution of problems of noise immunity, protection against information intrusions and imitating resistance. This, with relatively low economic costs, will significantly expand the capabilities of telecommunications systems in terms of information security. The effectiveness of the complex solution of information protection tasks from the positions of virtualization of the noise-immune encoding processes is experimentally proved in the work. The effectiveness of protection from information intrusions provided by virtual noise-immune codes and the effect of virtualization on the efficiency of the original noise-immune code were experimentally investigated. The obtained results show that virtual noise-resistant coding provides the effectiveness of protection from information intrusions, comparable with the efficiency of modern standards of cryptographic protection, with significantly lower complexity of practical implementation. In general, the results of experimental studies show that the virtualization of the process of noise-immune encoding from the perspective of the approach proposed in [1] opens an additional possibility of protecting information in the part of ensuring information security.Â